Apexification treatment on tooth with a history of trauma: A case report - Juniarti, Devi Eka; Anandita, Tiara; Tania, Cindy Grace; Prasetyo, Eric Priyo; Yuanita, Tamara (Conservative Dentistry Journal, 2024)
Background: Traumatic dental injuries to the teeth may result in pulpal and periapical disease. Most dental traumas occur in the 7 -10-year-old age group with incomplete apical root development. Apexification is the procedure to close the apex using bioactive material to create an apical plug. MTA can be used as a material of choice to treat open apex. Purpose: To perform an apexification of open apex with MTA apical plug. Case: A 30-year-old female patient with a chief complaint to fix her missing anterior filling and blackened tooth. The tooth had a history of trauma when the patient was 7 years old. One year ago, the tooth had intermittent pain so the tooth was treated and filled by another dentist. Case Management: Access opening is performed and apical gauging is determined. Then, working length was established. Debridement was done with H-file #80. Irrigation sequence with NaOCl 1,5% - Aquadest – EDTA 17% -aquadest. Ca(OH)2 dressing was given and temporary restoration was placed. On the second visit, temporary restoration was removed, followed by a root canal filled with MTA 3 mm from the apex using MAP carrier then confirmed with a radiograph. Conclusion: Trauma that occurs during tooth formation may cause an open apex that is treatable using an MTA plug.